Improved Risk-Adjusted Survival for Melanoma Brain Metastases in the Era of Checkpoint Blockade Immunotherapies: Results from a National Cohort - Iorgulescu, J. Bryan (Cancer Immunol Res, 2018)
The successes of checkpoint blockade immunotherapy (CBI) and BRAF(V600)-targeted therapy trials have generated substantial promise for revolutionizing the management of patients with advanced melanoma. However, because early clinical trials of CBIs and BRAF(V600)-targeted therapy either excluded or included disproportionately fewer cases of melanoma brain metastases (MBM), the survival benefit of these novel therapies for MBM remains unknown. We, therefore, evaluated the characteristics, management, and overall survival (OS) of patients who presented with cutaneous MBMs during 2010–2015 using the National Cancer Database, which comprises 70% of all newly diagnosed U.S. cancers. OS was analyzed with risk-adjusted proportional hazards and compared by Kaplan-Meier techniques. We found that 2,753 (36%) of patients presenting with stage 4 melanoma had MBMs. Following the 2011 FDA approvals for CBI and BRAF(V600)-targeted therapy, MBM patients demonstrated a 91% relative increase in 4-yr OS to 14.1% from 7.4% pre-approval (p<0.001). Post-approval, the proportion of MBM patients that received CBI rose from 10.5% in 2011 to 34.0% in 2015 (p<0.001). Initial CBI in MBM patients displayed an improved median and 4-yr. OS of 12.4 months (compared to 5.2 months; p<0.001) and 28.1% (compared to 11.1%), respectively. These benefits were pronounced in MBM patients without extracranial metastases, in which, CBI demonstrated improved median and 4-yr. OS of 56.4 months (compared to 7.7 months; p<0.001) and 51.5% (compared to 16.9%), respectively. Using a large national cohort composed of a “real-life” MBM treatment population, we demonstrated the dramatic OS improvements associated with novel checkpoint blockade immunotherapies.